Development of TaC-based transition metal carbide superlattices via compound target magnetron sputtering. (June 2023) - Schmid, Barbara; Koutná, Nikola; Hahn, Rainer; Wojcik, Tomasz; Polcik, Peter; Mayrhofer, Paul Heinz
Abstract: Transition metal carbides belong to ultra-high temperature ceramics and are particularly valued for their high thermal and mechanical stability as well as melting points of even above 4000 °C. However, a considerable limitation of these materials is their high inherent brittleness. Inspired by the success of nanolayered superlattice architecture—shown to enhance both hardness and toughness of transition metal (TM) nitrides—we developed superlattice films with TM carbides. Among these, density functional theory calculations suggest TaC/HfC and TiC/TaC to have a similar shear modulus mismatch of 23 and 19 GPa, but a different lattice parameter mismatch of 4.2 and 2.4%, respectively. Detailed transmission electron microscopy and X-ray diffraction show a pronounced superlattice structure for TiC/TaC with nominal bilayer periods Λnom of 2, 6, and 10 nm. Contrary, the TaC/HfC showed a more solid solution like characteristic for Λnom = 2 nm, and a clear superlattice structure for Λnom = 6 and 10 nmjap. While the hardness of the TaC/HfC coatings is between those of their constituents TaC (33.3 ± 1.9 GPa) and HfC (37.4 ± 3.2 GPa), the TiC/TaC superlattices outperform their constituents and clearly show a superlattice-effect with a peak of 44.1 ± 3.4 GPa at Λnom = 2 nm (TiC has 37.6 ± 3.1 GPa). Also the qualitative fracture behavior investigation with 450-mN-loaded cube corner indentation yield the TiC/TaC superlattices to be superior to the TaC/HfC as well as the monolithically prepared TiC, TaC, and HfC coatings. Highlights: Non-reactive magnetron sputtering allows to grow fcc structured TaC, HfC, and TiC coatings and their superlattices. Superlattice effect for hardness and fracture toughness, was found for TaC-based transition metal carbide superlattices. TiC/TaC superlattices exhibit a hardness peak at a bilayer period of 2 nm a, exceeding both monolithic constituents The combination of TiC and TaC is superior to that of HfC and TaC in terms of hardness as well as fracture resistance